TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN ALOKASI DANA DESA (ADD) DI KECAMATAN MOYO HILIR KABUPATEN SUMBAWA BESAR - Baiq Kisnawati; Yuli Astini; Riri Nagita Oktaviani (Valid: Jurnal Ilmiah, 2018)
This study aims to find out the "Transparency and Accountability of Financial Management of Village Fund Allocation (ADD) in Moyo Hilir Sub-district of Sumbawa Besar Regency". The type of research is descriptive, the population used is the village apparatus and the village community residing in 10 villages in Moyo Hilir sub-district of Sumbawa Besar Regency. Sampling using purposive sampling with certain considerations. The sample of 140 respondents consists of 40 village apparatus (village head, village secretary, village treasurer and head of village development) and 100 people from society who understand about ADD financial management. The data used is quantitative data, sourced from primary data and secondary data. The results show that the transparency of financial management of ADD when viewed from planning and implementation aspect, the transparency is good or has been transparent. This is indicated by the respondent's answer 96.73% answered "Yes" for the planning aspect and 85.35% answered "Yes" for the implementation aspect. This is also evidenced by the participation of the community in the Village Development Planning Meeting (Musrenbangdes). While the accountability of the financial management of ADD in terms of implementation and supervision and accountability has also been good or accountable. It is shown 86.67% respondents answered "Yes" for implementation aspect and 94,17% responded "Yes" to supervision and responsibility aspect. This is evidenced also because the village government is always accountable for all activities of the use of ADD in the form of Accountability Report (LPJ)